On the acoustic emission in moisted concrets and the method of its practical application - KOŁTOŃSKI, W. (Archives of Acoustics, 1990)
The paper presents an attempt to explain mechanism of acoustic emission apperance due to water infiltration into the concrete. Experimental procedure of the V tests concerning this phenomenon is presented and obtained results are suported. Practical applications of the presented tests in civil engineering is also discussed.